Taxonomy of Salamanders of the Family Plethodontidae (Amphibia: Caudata) - Wake, David B. (Zootaxa, 2012)
Several recent publications have made recommendations for changes in the taxonomy of plethodontid salamanders. Here formal taxonomic proposals are made, in accordance with the Code, regarding family-group taxa. Subfamilies Hemidactyliinae and Plethodontinae are recognized, the former with four tribes and the latter with five tribes. Genera are assigned to the tribes, and subgenera are recognized in the genera Batrachoseps, Bolitoglossa, Hydromantes, Oedipina and Plethodon.